2011
DOI: 10.1183/09031936.00182010
|View full text |Cite
|
Sign up to set email alerts
|

Is multidrug-resistant tuberculosis on the rise in Mozambique? Results of a national drug resistance survey

Abstract: takes place only once the tubes are in the laboratory. If we consider only the samples sent from regional or remote sources, the rate of indeterminate test result is still very low (one (0.3%) out of 317). The use of T-Cell Xtend TM for all samples shipped overnight is likely to have had a beneficial effect on older samples. The cold weather conditions had no influence on the rate of indeterminate results (all samples were sent and processed in winter). The number of tests performed in very young or very old p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 6 publications
1
22
1
3
Order By: Relevance
“…As presented in Fig.3, except for two studies (from Swaziland and Mozambique) (23, 33), all other studies showed the association of MDR-TB to HIV positives or HIV negatives with an overall RR of 1.0 and 95% CI, 0.78 to 1.36. When any of the studies were withdrawn from the analysis, the overall risk ratio ranged between 0.94 and 1.06.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…As presented in Fig.3, except for two studies (from Swaziland and Mozambique) (23, 33), all other studies showed the association of MDR-TB to HIV positives or HIV negatives with an overall RR of 1.0 and 95% CI, 0.78 to 1.36. When any of the studies were withdrawn from the analysis, the overall risk ratio ranged between 0.94 and 1.06.…”
Section: Resultsmentioning
confidence: 83%
“…However, when we look at the findings in the individual studies, fewer resistant cases were found with ethambutol in the new than in the previously TB treated cases (15–17, 20, 23, 29, 31, 33, 39). Could its bacteriostatic nature (mycobacterial cell wall biosynthesis inhibition) explain why Mycobacterium TB strains became highly resistant to ethambutol among the previously treated?…”
Section: Discussionmentioning
confidence: 94%
“…This further suggests that rural areas might act as a possible source for the generation of multi drug-resistant TB (MDR-TB), given higher drug resistance rates have been repeatedly described in retreatment cases. 14,15 Tuberculosis programmes in rural areas have been scarcely reported although the knowledge of the epidemiologic situation in such areas is key to design and implement TB control policies. 16 We aimed to evaluate the outcomes and identify implementation challenges of the TB programme in a remote rural African district.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, an estimated 440,000 new cases of MDR-TB occurred worldwide, but only about 13% of these cases were detected and subsequently enrolled in treatment (Stop TB Partnership, 2012). National studies from Mozambique (Samo Gudo et al, 2011) and Swaziland (Sanchez-Padilla et al, 2012) reported that the proportion of MDR-TB infections was significantly higher among PLH, when compared to HIVuninfected individuals. Further, Sanchez-Padilla and colleagues (2012) found that PLH were twice as likely to be infected with MDR-TB when compared to HIV-negative individuals.…”
Section: Discussionmentioning
confidence: 98%